1977
DOI: 10.1109/jqe.1977.1069317
|View full text |Cite
|
Sign up to set email alerts
|

Metal-clad waveguide as cutoff polarizer for integrated optics

Abstract: 141to DFB and DBR lasers as well as orthogonal radiation from grating couplers. Solutions for all Bragg orders up to the fourth and various blazing angles of a triangular grating were given and applied to determine reflection for a DBR laser and longitudinal mode thresholds and wavelengths in a DFB laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 19 publications
(5 reference statements)
0
13
0
1
Order By: Relevance
“…The effective index of these modes is a strong function of metal thickness in the low contrast region and hence this can be tuned by the change in metal thickness. This property has been used in the early polarizer designs [5]. It is this mode which also plays a vital role in the recently designed polarizers for silicon on insulator (SOI) waveguide [13].…”
Section: The Antisymmetric Bound ( ) Modementioning
confidence: 99%
See 2 more Smart Citations
“…The effective index of these modes is a strong function of metal thickness in the low contrast region and hence this can be tuned by the change in metal thickness. This property has been used in the early polarizer designs [5]. It is this mode which also plays a vital role in the recently designed polarizers for silicon on insulator (SOI) waveguide [13].…”
Section: The Antisymmetric Bound ( ) Modementioning
confidence: 99%
“…A metal-cladplasmonic waveguide can be designed to act as a polarizer in integrated optical circuits [3][4][5][6]12,13]. The metallic layer provides polarization discrimination because losses for TM modes were higher than losses for TE polarized modes due to penetration of the TM fields into the metal.…”
Section: In Waveguide Polarizersmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that he effective mode index of the TE mode is usually less than that of the TM mode. Therefore, an effective decrease in the waveguide refractive index, or it thickness, would cut-off the TE mode before cutting-off the TM mode [7,8].…”
Section: Three Layer Slab Waveguidementioning
confidence: 99%
“…Recently metal-clad optical waveguides [13][14][15][16][17][18] have been studied theoretically, experimentally and technically because these provide potential applications, such as connecting the optical components to other circuits, protecting the optical devices against stray light and heat sinking. Metallic -cladding structure on an optical waveguide is known as a TE-mode pass polarizer and is commercially applied to various optical devices [16,17].…”
Section: Introductionmentioning
confidence: 99%